Digitalization: Productivity - Jeffrey Mollins; Temel Taskin (Bank of Canada, 2023)
We examine the relationship between digitalization and productivity, the factors that influence this relationship, and how digitalization's effect on productivity could change firm behaviour.
Keywords: E; E2; L; L1; L11; O; O4; O47; O5; O51; 330; Digitalization; Productivity